Localization of Retinal Ca2+/Calmodulin-Dependent Kinase II-β (CaMKII-β) at Bipolar Cell Gap Junctions and Cross-Reactivity of a Monoclonal Anti-CaMKII-β Antibody With Connexin36 - Tetenborg, Stephan; Yadav, Shubhash Chandra; Brüggen, Bianca; Zoidl, Georg R.; Hormuzdi, Sheriar G.; Monyer, Hannah; van Woerden, Geeske M.; Janssen-Bienhold, Ulrike; Dedek, Karin (Frontiers in Molecular Neuroscience, 2019)
Neuronal gap junctions formed by connexin36 (Cx36) and chemical synapses share striking similarities in terms of plasticity. Ca2+/calmodulin-dependent protein kinase II (CaMKII), an enzyme known to induce memory formation at chemical synapses, has recently been described to potentiate electrical coupling in the retina and several other brain areas via phosphorylation of Cx36. The contribution of individual CaMKII isoforms to this process, however, remains unknown. We recently identified CaMKII-β at electrical synapses in the mouse retina. Now, we set out to identify cell types containing Cx36 gap junctions that also express CaMKII-β. To ensure precise description, we first tested the specificity of two commercially available antibodies on CaMKII-β-deficient retinas. We found that a polyclonal antibody was highly specific for CaMKII-β. However, a monoclonal antibody (CB-β-1) recognized CaMKII-β but also cross-reacted with the C-terminal tail of Cx36, making localization analyses with this antibody inaccurate. Using the polyclonal antibody, we identified strong CaMKII-β expression in bipolar cell terminals that were secretagogin- and HCN1-positive and thus represent terminals of type 5 bipolar cells. In these terminals, a small fraction of CaMKII-β also colocalized with Cx36. A similar pattern was observed in putative type 6 bipolar cells although there, CaMKII expression seemed less pronounced. Next, we tested whether CaMKII-β influenced the Cx36 expression in bipolar cell terminals by quantifying the number and size of Cx36-immunoreactive puncta in CaMKII-β-deficient retinas. However, we found no significant differences between the genotypes, indicating that CaMKII-β is not necessary for the formation and maintenance of Cx36-containing gap junctions in the retina. In addition, in wild-type retinas, we observed frequent association of Cx36 and CaMKII- with synaptic ribbons, i.e., chemical synapses, in bipolar cell terminals. This arrangement resembled the composition of mixed synapses found for example in Mauthner cells, in which electrical coupling is regulated by glutamatergic activity. Taken together, our data implies that CaMKII-β may fulfill several functions in bipolar cell terminals, regulating both Cx36-containing gap junctions and ribbon synapses and potentially also mediating cross-talk between these two types of bipolar cell outputs.